Islam pascakolonial : perselingkuhan agama, kolonialisme, dan liberalisme - Baso, Ahmad, 1971- (Bandung : MIZAN, 2005)
Issues of religions, Islamic law, and development of Islam after Dutch colonial in Indonesia.
Includes bibliographical references (p. [391]-411) and index.
Keywords: Islam -- Indonesia -- 20th century